1989
DOI: 10.1093/nar/17.19.7771
|View full text |Cite
|
Sign up to set email alerts
|

Acis-acting transcription element of the c-mycgene can assume an H-DNA conformation

Abstract: I have used chemical probes and an oligonucleotide-association assay to determine the structure of a nuclease-sensitive, c-myc DNA region. I find that this DNA region can form a triplex-single stranded conformer in vitro--the H-DNA conformer. This DNA region has been shown previously to be a positive, cis-acting transcription element of the c-myc gene and to bind nuclear factors, including a base-paired ribonucleoprotein. Therefore, H-DNA may be a functionally important in vivo topoisomer where the H-DNA and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…This study (Fig. 1B) and previous reports (10) have suggested that the 23-bp sequence from the promoter region of the c-myc gene in the human genome can adopt an H-DNA structure. Its control derivative, pMycAG, which differs from pcMyc by 2 bp, did not adopt H-DNA structures under the conditions used in the S1 and P1 nuclease assays, as expected.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study (Fig. 1B) and previous reports (10) have suggested that the 23-bp sequence from the promoter region of the c-myc gene in the human genome can adopt an H-DNA structure. Its control derivative, pMycAG, which differs from pcMyc by 2 bp, did not adopt H-DNA structures under the conditions used in the S1 and P1 nuclease assays, as expected.…”
Section: Discussionsupporting
confidence: 83%
“…The conformation of H-DNA has been probed in vivo by using both triplex antibodies and fluorescently labeled single-stranded DNA oligonucleotides (8,9). Unlike other DNA secondary structureforming sequences, which are typically located in intergenic or intronic regions, H-DNA-forming sequences are found most frequently in promoters and exons and have been found to be involved in regulating the expression of several disease-linked genes (10,11). For example, the human c-myc gene, which is often translocated and overexpressed in tumors, contains an H-DNA-forming sequence in its promoter (10,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Certain "fragile site" or "hotspot" regions of the genome are mapped in or near sequences that have the potential to adopt non-B DNA conformations. For example, a segment in the promoter of the human c-MYC gene capable of adopting H-DNA [112], overlaps with the one of major breakage hotspots found in c-MYC-induced lymphomas and leukemias [113][114][115][116][117]. An H-DNA structure is also found in the BCL-2 gene major breakpoint region in follicular lymphomas, and disruption of the H-DNA conformation markedly reduces the frequency of translocation events, supporting a role for the H-DNA structure in the formation of the oncogenic translocations [118].…”
Section: Detecting H-dna In Vitro and In Vivomentioning
confidence: 99%
“…Mirror-repeats occur randomly in prokaryotes, but are three to six times more frequent in eukaryotic genomes (Schroth and Ho, 1995). Specific H-DNA forming sequences have been identified in multiple promoter regions with documented effects on gene expression of several disease related genes, including c-myc (Kinniburgh, 1989) and c-Ki-ras (Pestov et al, 1991). As with Z-DNA, the repeating sequence motif of H-DNA appears to be a source of genetic instability resulting from double-strand breaks.…”
Section: H-dna: Three's a Crowdmentioning
confidence: 99%